Reflections of aged participating in the health promotion groups concerning the ageing and the quality of life - Tahan, Jennifer; Carvalho, Antonio Carlos Duarte de (Saúde e Sociedade, 2010)
The progressive growth in the number of aged people over the last decades promoted the development of an interest in studying ageing and of the factors associated with the aged people's quality of life. Important advancements in health have been conquered in Brazil and the Family Health Strategy appeared with the strength to establishing the participation of the community and the comprehensiveness of the actions. Therefore, the purpose of this study was to analyze the perceptions of aged individuals regarding their quality of life after joining the Health Promotion Groups. The study used a qualitative approach and data collection was performed by means of semi-structured interviews and participant observation. Content analysis was performed using the thematic analysis technique, resulting in six major themes: Feelings about what it is like to be aged in Brazil; Health Satisfaction; Meanings about quality of life; Life satisfaction; The importance of social and leisure activities for quality of life; Health Promotion Groups. These suggest that the citizens of the research value independence and autonomy in performing their activities and report a healthy life and having adequate behavior concerning their health care, and also highlight that leisure activities, participating in health promotion groups and good relationships are essential to achieve fulfillment in life, pointing with respect to a vision of positive health, in which such activities, especially their participation in health promotion groups, were extremely important for their quality of life and for creating a social health care network that integrated the community and the services of health.